Bibliometric Analysis of Competitive Advantage - Loso Judijanto (Westscience Press, 2026)
Competitive advantage has emerged as an essential aspect of strategic management that helps firms build their capabilities and sustain themselves in volatile market conditions. In this study, an attempt is made to conduct a bibliometric analysis to investigate the intellectual structure, trends in research, key contributors, and emerging themes in competitive advantage research. The data was collected from Scopus database using the keywords